902 Prevalence and factors associated with road traffic crash among taxi drivers in mekelle town, Northern Ethiopia, 2014: a cross sectional study. (1st September 2016) - Asefa, Nigus Gebremedhin; Ingale, Lalit; Shumey, Ashenafi; Yang, Hannah
Abstract : Objectives: The 2013 World Health Organisation Status Report on Road Safety estimated that approximately 1.24 million deaths occur annually due to road traffic crashes with most of the burden falling on low- and middle-income countries. The objective of this research is to study the prevalence of road traffic crashes in Mekelle, Tigray, Northern Ethiopia and to identify risk factors with the ultimate goal of informing prevention activities and policies. Methods: This study used a cross-sectional design to measure the prevalence and factors associated with road traffic crashes among 4-wheeled minibus (n = 130) and 3-wheeled Bajaj (n = 582) taxi drivers in Mekelle, Ethiopia. Bivariate and multivariate logistic regression were used to evaluate the association between risk factors and drivers' involvement in a road traffic crash within the 3 years prior to the survey. Results: Among the 712 taxi drivers, 26.4% (n = 188) of them reported involvement in a road traffic crash within the past 3 years. Drivers who listened to mass media had decreased likelihood of road traffic crash involvement (Adjusted odds ratio, AOR: = 0.51, 0.33–0.78), while speedy driving (AOR: = 4.57, 3.05–7.44), receipt of a prior traffic punishment (AOR: = 4.57, 2.67–7.85), and driving a mechanically faulty taxi (AOR: = 4.91, 2.81–8.61) were strongly associated with road traffic crash involvement. Receiving mobile phone calls while driving (AOR: = 1.91, 1.24–2.92) and history of alcohol use (AOR: = 1.51, 1.00–2.28) were also associated with higher odds of road traffic crash involvement. Conclusion: The results of this study show that taxi drivers in Mekelle habitually place themselves at increased risk of road traffic crashes by violating traffic laws, especially related to speedy driving, mobile phone use, and taxi maintenance. This research can be used to support reevaluation of the type, severity, and enforcement of traffic violation penalties.